1936
DOI: 10.5962/bhl.title.64299
|View full text |Cite
|
Sign up to set email alerts
|

Parasites and predators of the Mexican bean beetle in the United States

Abstract: Paradexodes epilachnae Aid Phorocera claripennis Macq Unknown species Do Do Sarcophagidae: Helkobia helkis Towns Sarcophaga latisterna Park Phoridae: Megaselia sp Bacteria: Coccobacillus sp Streptococcus sp Unknown Fungi imperfecti: Beauveria globulifera Cephalothecium sp Cordyceps militaris (L.) Link.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Predatory insects known to hunt phytophagous ladybirds include beetles (entomophagous Coccinellidae, Carabidae, Cantharidae), true bugs (Anthocoridae, Nabidae, Reduviidae, Pentatomidae, Lygaeidae), neuropterans (Chrysopidae, Myrmeleontidae), butterfl ies (larvae of some Noctuidae), earwigs (Forfi culidae) and ants (Formicidae) (Howard & Landis 1936, Ohgushi 1986. Ants are also known as occasional predators of predatory coccinellids (Sloggett et al 1999, Majerus et al 2007 ), but the majority of interactions between these two groups of insects are of a competitive nature.…”
Section: Morphological a Nti -P Redator A Daptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Predatory insects known to hunt phytophagous ladybirds include beetles (entomophagous Coccinellidae, Carabidae, Cantharidae), true bugs (Anthocoridae, Nabidae, Reduviidae, Pentatomidae, Lygaeidae), neuropterans (Chrysopidae, Myrmeleontidae), butterfl ies (larvae of some Noctuidae), earwigs (Forfi culidae) and ants (Formicidae) (Howard & Landis 1936, Ohgushi 1986. Ants are also known as occasional predators of predatory coccinellids (Sloggett et al 1999, Majerus et al 2007 ), but the majority of interactions between these two groups of insects are of a competitive nature.…”
Section: Morphological a Nti -P Redator A Daptationsmentioning
confidence: 99%
“…Natural enemies of ladybird beetles 387 Belshaw (1993); 3, Berry & Parker (1949); 4, Beyene et al (2007); 5, Boucek (1988); 6, Ceryngier & Hodek (1996); 7, Compere (1938); 8, Crawford (1912); 9, Delucchi (1954); 10, Disney et al (1994); 11, Domenichini (1957); 12, Elliott & Morley (1907); 13, Hemptinne (1988);14, Hodek (1973); 15, Howard & Landis (1936); 16, Husain & Khan (1986); 17, Kerrich (1973); 18, Klausnitzer (1967);19, Lotfalizadeh (2010); 20, Marlatt (1903); 21, Nalepa & Kidd (2002);22, Nikol 'skaya (1934); 23, Noyes (2011);24, O 'Hara (2009);25, Pankanin-Franczyk & Ceryngier (1999); 26, Patnaik & Mohapatra (2004); 27, Radwan & Lovei (1982); 28, Richerson (1970); 29, Richter (1971); 30, Riddick et al (2009); 31, Risbec (1951); 32, Schaefer & Semyanov (1992); 33, Shima et al (2010); 34, Smirnoff (1957); 35, Usman & Thontadarya (1957); 36, Yinon (1969); 37, R. Comont (unpublished). …”
Section: Natural Enemies Of Ladybird Beetles 385mentioning
confidence: 99%
“…The list of natural enemies of the Mexican bean beetle is considerable, but early workers found little inßuence on Mexican bean beetle population dynamics (Howard andEnglish 1924, Howard andLandis 1936). Despite some positive results using the parasite Pediobius foveolatus (Crawford) (Angalet al 1968), the parasites could not survive the winter in the Þeld, and maintenance in laboratory was required during the winter (Stevens et al 1975).…”
mentioning
confidence: 97%
“…Both direct toxicity (via exposure to or ingestion of treated snap beans) and secondary toxicity (via ingestion of intoxicated prey) were tested because P. maculiventris is known to feed on snap bean plants and E. varivestis larvae, pupae, and adults (Howard andLandis 1936, O'Neil andWiedenmann 1990). Toxicity of seed-treatment grown plants to P. maculiventris was evaluated in three ways: 1) exposure of P. maculiventris to plants alone; 2) exposure to prey (E. varivestis third instars and adults) alone; and 3) exposure to plants and prey together.…”
Section: Direct and Secondary Toxicity To P Maculiventrismentioning
confidence: 99%
“…However, dead adult and larval E. varivestis were found in all containers, and predation was witnessed in both treatments, suggesting that all P. maculiventris fed on beetles. Additionally, previous research has demonstrated that P. maculiventris readily feed on E. varivestis larvae and adults in cages staged in laboratories and greenhouses (Howard and Landis 1936, O'Neil 1989, Wiedenmann and O'Neil 1991.…”
Section: Direct and Secondary Toxicity To P Maculiventrismentioning
confidence: 99%